MOTIVASI DAN HASIL BELAJAR AL-QUR'AN HADITS MELALUI MODEL PEMBELAJARAN BERBASIS PORTOFOLIO - Ah. Slamet Budi Harsono (UNISAN JURNAL, 2024)
The point of this exploration is to decide the inspiration and results of learning Al-Qur'an Hadith through a portfolio-based learning model at MI Matlaul Anwar. In the mean time, this examination utilizes a subjective illustrative exploration technique. Information assortment was done utilizing perception and documentation techniques. Information investigation was done utilizing triangulation, to be specific information decrease, information show and check. In view of the consequences of information examination in the conversation, ends can be drawn. In view of the consequences of information examination in the conversation of the past section, it tends to be reasoned that MI Matlaul Anwar can foster inspiration and learning results for the Al-Qur'an and Hadith through a portfolio-based learning model, specifically dynamic understudy learning. , agreeable understudy learning gatherings, inventive instructing, revelation strategies and request techniques. Aside from that, the creator might want to contribute considerations as ideas as follows: 1) for educators of Al-Qur'an Hadith subjects to keep up with their techniques in further developing understudy learning results persistently and constantly so they affect further developing understudy learning results. further develop understudy learning results. further develop learning results. MI Matlaul Anwar understudies are urged to work on their learning and skill by taking part in different positive and productive exercises with the goal that they affect understudy learning results in the educating and growing experience